Integrating Islamic Studies into English Language Learning for Qur’anic Studies Students: A Content-Based Approach at UIN Datokarama Palu - Sahril Sahril; Nurasia Munir (Civiliza Publishing, Indonesia., 2025)
English language instruction in Islamic higher education is increasingly expected to support students’ disciplinary learning and future academic engagement in global scholarly communities. However, English courses are often delivered using general materials that are not closely related to students’ fields of study, resulting in limited relevance and motivation. This study aims to explore the integration of Islamic Studies content into English language learning for students of the Qur’anic Sciences and Tafsir Department at UIN Datokarama Palu through a Content-Based Instruction (CBI) approach. Employing a qualitative descriptive design, the study collected data through classroom observations, document analysis, and student reflections during the implementation of English learning activities based on Islamic Studies topics, including Qur’anic themes, tafsir discourse, Islamic ethics, and contemporary Muslim issues. The findings indicate that the integration of discipline-specific content enhances students’ motivation to learn English, enriches their academic vocabulary, improves reading comprehension, and increases their confidence in discussing Islamic topics in English. Students also demonstrated greater engagement in classroom discussions because the learning materials were closely connected to their academic background and interests. These findings suggest that Content-Based Instruction provides meaningful and contextualized learning experiences by simultaneously promoting language development and disciplinary knowledge acquisition. The study concludes that integrating Islamic studies into English language learning is an effective strategy for improving English proficiency among Qur’anic Studies students and can serve as a practical model for English for Specific Purposes (ESP) programs in Islamic higher education institutions.